Gambaran Pola Asuh Orangtua dalam kaitannya dengan Motivasi Belajar Anak - Marsidi, Sitti Rahmah; Agustin, Anindyarini; Novitasari, Astrid; Ryan, Muhamad; Nurfikriana, Raysya; Handayani, Refiyanti; Setiawati, Vernika (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2021)
The purpose of this study was to obtain an overview of parenting related to children's learning motivation, the type of parenting that is effective in motivating children's learning, and to know the role of parenting in influencing children's learning motivation. This study uses a qualitative approach, with 5 children and 5 parents as research subjects. Collecting data using observation, interviews, and other complementary data. The results of the study in the form of parenting and parental participation have an effect on children's learning motivation. Children with democratic parenting have good and sufficient motivation to learn. Children with permissive parenting have less motivation. The application of good parenting can be realized through treatment, attention, fulfillment of needs, and attitudes of parents. The appropriate treatment is in educating children, which will later make it easier to increase children's motivation when learning.